The first book of fashion the book of clothes of Matthäus and Veit Konrad Schwarz of Augsburg - Schwarz, Matthäus 1497-1574; Schwarz, Veit Konrad 1541-1587; Tiramani, Jenny 19XX- (Bloomsbury Academic, 2015)
An obsession with fashion is nothing new. Throughout history, dress has mesmerised with its power to charm and communicate identity and status. In this first English translation of an extraordinary historical document - the earliest known book of fashion - fashion-conscious Renaissance man Matthäus Schwarz and his son Veit Konrad chronicle their lives through the clothes they wore. Lavishly illustrated, The First Book of Fashion recaptures the experience of sixteenth-century life through the rich intricacies of dress and its cultural meaning. The book unpicks the fabrics, cuts, colours and detail of these remarkable illustrations and their brilliant captions handwritten by Schwarz, arguably making him the first fashion blogger. Historians Ulinka Rublack and Maria Hayward bring the original manuscript to life with new, insightful commentaries alongside the original text, providing an unparalleled portrait of sixteenth-century dress and culture in context. Including a specially-designed pattern by Olivier award-winning costume designer Jenny Tiramani, from which readers can recreate one of Schwarz's original garments, this is a valuable resource for everyone from scholars to designers to fashion enthusiasts